2008
DOI: 10.1186/1472-6963-8-98
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents perception of reproductive health care services in Sri Lanka

Abstract: Background: Adolescent health needs, behaviours and expectations are unique and routine health care services are not well geared to provide these services. The purpose of this study was to explore the perceived reproductive health problems, health seeking behaviors, knowledge about available services and barriers to reach services among a group of adolescents in Sri Lanka in order to improve reproductive health service delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
86
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 13 publications
13
86
0
3
Order By: Relevance
“…A previous study indicated that there are problems with the skills, confidence and attitudes of teachers towards ASRH teaching [22]. Few teachers are involved in sexual discussions [23,24] and they commonly rely on health professionals to provide this education, however health professionals also lack the confidence to deliver sex education [22]. Dawson et al [22] identified the value of a collaborative approach to ASRH education and this has clear benefits, however all those involved need to receive adequate training to equip them with the knowledge and skills they require and adequate ongoing support at a local and national level.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that there are problems with the skills, confidence and attitudes of teachers towards ASRH teaching [22]. Few teachers are involved in sexual discussions [23,24] and they commonly rely on health professionals to provide this education, however health professionals also lack the confidence to deliver sex education [22]. Dawson et al [22] identified the value of a collaborative approach to ASRH education and this has clear benefits, however all those involved need to receive adequate training to equip them with the knowledge and skills they require and adequate ongoing support at a local and national level.…”
Section: Discussionmentioning
confidence: 99%
“…According to the world health organization (WHO), an adolescent is a person within the age range of 11 to 19 years old (1). More than 1.2 billion people in the world are adolescents (2).…”
Section: Contextmentioning
confidence: 99%
“…In a study by [3] participant's lack of confidence in solving reproductive and sexual health related problems was linked to unawareness of reproductive and sexual health which they could have had access to at the A/YFRHS facilities. They were unanimous in suggesting that increased awareness about adolescent and youth health services would promote better utilization of services.…”
Section: How Knowledge Affects Utilization Of A/yfrhsmentioning
confidence: 99%
“…These youths due to their rapid development are vulnerable to a lot of health risks and most of these risks are related to their sexual and reproductive health [2]. The reproductive health (RH) services in the family health program are traditionally targeted at married couples [3] but some are now accessed by youths in some health facilities. Currently, youth friendly services are developing in Nigeria.…”
Section: Introductionmentioning
confidence: 99%